Vráble, Slowakei. Herausbildung und Niedergang des frühbronzezeitlichen Siedlungszentrums – Untersuchungen zu Wirtschaft, Sozialstruktur und politischer Organisation eines Sozialverbandes und seines Umfeldes. Überblick und die Arbeiten in der Siedlung 2017 - Skorna, Henry; Kalmbach, Johannes; Bátora, Josef (e-Forschungsberichte des DAI, 2018)
The Early Bronze Age fortified settlement of Vráble, one of the largest in the Pannonian basis, is the target of a multi-disciplinary research program since the past decade. Funded by the German Archaeological Institute (DAI), methods including geomagnetics, aerial photography, Electrical Resistivity Tomography, Ground-Penetrating Radar, and surface collection as well as coring, soil chemistry, and targeted excavation have been applied to explore the settlement and the nearby contemporary cemetery. As a result of this research, we propose a model with four phases of settlement development. Founded at the end of the 3rd millennium BC, Vráble began as a 0.3 ha fortified village, fitting into the typical settlement structure of the beginning of the Early Bronze Age in the region. Over time, the settlement rapidly grew to a size of 12 ha before being destroyed by a fire event around 1730 BC. It was then rebuilt as a much smaller (1.2 ha), heavily fortified village which lasted only ca. 100 years before the site was abandoned. In the last field campaign of the funding period in 2017, the excavation of one house site was completed. The aim was to verify the above-mentioned settlement sequence and to gather further data. During the excavation it became clear that the proposed model can be confirmed. Furthermore, due to the excellent preservation, we gained additional information regarding the construction method of the houses and their surroundings. We can reconstruct Early Bronze Age houses (12 m long, 5.5 m wide) as having wattle-and-daub walls and alleys with wooden boardwalks. The finding of two impressive burnt wicker baskets containing one vessel set (seven nearly complete vessels) and hundreds of burnt cereal grains suggests that the Bronze Age inhabitants of Vráble frequently used wicker baskets as storage vessels. The in situ finds of one cushion stone and one clay nozzle add to the existing evidence of Vráble being a regional centre of metallurgy.